Integrated Communication System: Gesture and Language Acquisition in Typically Developing Children and Children With LD and DLD - Lüke, Carina; Ritterfeld, Ute; Grimminger, Angela; Rohlfing, Katharina J.; Liszkowski, Ulf (Frontiers in Psychology, 2020)
Gesture and language development are strongly connected to each other. Two types of gestures in particular are analyzed regarding their role for language acquisition: pointing gestures and iconic gestures. With the present longitudinal study, the predictive values of index-finger pointing at 12 months and the comprehension of iconic gestures at 3;0 years for later language skills in typically developing (TD) children and in children with a language delay (LD) or developmental language disorder (DLD) are examined.Forty-two monolingual German children and their primary caregivers participated in the study and were followed longitudinally from 1;0 to 6;0 years. Within a total of 14 observation sessions, the gestural and language abilities of the children were measured using standardized tests and parent questionnaires as well as ad-hoc tests and semi-natural interactions with the caregivers. At the age of 2;0 years, 10 of the 42 children were identified as having a LD. The ability to point with the extended index finger at 1;0 year is predictive for language skills at 5;0 and 6;0 years. This predictive effect is mediated by the language skills of the children at 3;0 years. The comprehension of iconic gestures at 3;0 years correlates with index-finger pointing at 1;0 year and also with earlier and later language skills. It mediates the predictive value of index-finger pointing at 1;0 year for grammar skills at 5;0 and 6;0 years. Children with LD develop the ability to understand the iconicity in gestures later than TD children and score lower in language tests until the age of 6;0 years. These language differences between the two groups of children remain partially until the age of 5;0 years even when the two children with persistent DLD within the group of children with LD are excluded from analyses. Beyond that age, no differences in the language skills between children with and without a history of LD are found when children with a persistent DLD are excluded.The findings support the assumption of an integrated speech-gesture communication system, which functions similarly in TD children and children with LD or DLD, but with a time delay.